Apricot pip shells used as aggregate replacement - Yildiz, Servet; Emiroglu, Mehmet; Atalar, Onur (Journal of Civil Engineering and Management, 2012)
To improve the undesired characteristics of concrete, for example high CO2 emission and loss of strata from quarrying of raw materials, environmentally hazardous solid waste could be utilized as cement, sand and/or aggregate replacement. Apricot Pip Shells (APSs) are an environmental problem mainly in the region where apricots are cultivated. The shells are burnt as a fuel by local people in this region. An alternative use for this waste material would be for aggregate replacement in concrete as reported in this paper. In this study, limestone aggregate were substituted by different percentage of APS in the prepared concrete mixes. Unit weight, compressive and tensile strength tests were conducted on the specimens. A decrease was observed in the strength development of the concrete containing APS. This may have resulted from the weak adherence between APSs and cement paste in the interfacial transition zone. However, the unit weight of the concrete decreased for higher APS content in the mix.